REVISITING A COMPARATIVE STUDY OF MELATONIN WITH PLACEBO IN ATTENUATION OF HEMODYNAMIC RESPONSES TO LARYNGOSCOPY AND INTUBATION - Sengul, Ilker; Sengul, Demet (Sanamed, 2025)
No abstract available
Keywords: .